2012
DOI: 10.1002/ana.23651
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4‐specific T cells in neuromyelitis optica exhibit a Th17 bias and recognize Clostridium ABC transporter

Abstract: Objective Aquaporin-4 (AQP4)-specific autoantibodies in neuromyelitis optica (NMO) are IgG1, a T cell-dependent Ig subclass, indicating AQP4-specific T cells participate in NMO pathogenesis. Our goal was to identify and characterize AQP4-specific T cells in NMO patients and healthy controls (HC). Methods Peripheral blood T cells from NMO patients and HC were examined for recognition of AQP4 and production of proinflammatory cytokines. Monocytes were evaluated for production of T cell-polarizing cytokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
289
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(304 citation statements)
references
References 49 publications
6
289
1
3
Order By: Relevance
“…Third, it is possible that C. perfringens might participate in more than one CNS autoimmune disease. In this regard, one year after we identified the potential link between C. perfringens and NMO,3 C. perfringens was implicated in MS pathogenesis 19. Another study found that Clostridium species within clusters XIVa and IV, which do not contain C. perfringens (a member of cluster I), are reduced in relapsing–remitting MS patients 20.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, it is possible that C. perfringens might participate in more than one CNS autoimmune disease. In this regard, one year after we identified the potential link between C. perfringens and NMO,3 C. perfringens was implicated in MS pathogenesis 19. Another study found that Clostridium species within clusters XIVa and IV, which do not contain C. perfringens (a member of cluster I), are reduced in relapsing–remitting MS patients 20.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, we observed that T cells from NMO patients proliferate more vigorously in response to AQP4 than T cells from healthy controls (HC) 3. In NMO, T‐cell recognition of the immunodominant determinant peptide (p) 63–76 was associated with Th17 polarization.…”
mentioning
confidence: 98%
“…The composition of the gut microbiota varies between monozygotic twins (27) and influences the development of the immune system (28). The composition of the gut commensal microbiota has recently been identified as an environmental factor that can trigger CNS demyelinating autoimmune disease (14,29,30 …”
Section: Foxp3mentioning
confidence: 99%
“…In contrast to EAE and MS, complement-activating autoantibodies against aquaporin 4 (AQP4), the predominant CNS water channel, have been implicated in the induction of inflammatory demyelination in humans with NMO (13). More recently, AQP4-specific T cells exhibiting a Th17 bias and displaying cross-reactivity to the gut commensal bacteria Clostridium perfringens have also been implicated (14,15).…”
mentioning
confidence: 99%
“…Initial therapeutic targets in NMO were against B cells given their role in antibody production. Recent efforts have helped to clarify the role of other immune cells in this process, including Th17 cells in producing these destructive lesions [47]. IL-6, which promotes antibody production in activated B cells as well as Th17 differentiation, was present in elevated levels in the serum and CSF has been shown to be elevated in patients with NMO, especially during relapse [48].…”
Section: Neuromyelitis Optica (Nmo)mentioning
confidence: 99%